Effect of Coarse Aggregate Size on Shear Behavior of Self-Compacting Concrete and Conventional Concrete Beams - A. Ismael, Murtada; J. Abd, Haitham; A. Hameed, Adham (International Journal of Engineering and Technology, 2018)
This research presents an experimental study to investigate the effect of coarse aggregate maximum size on the shear behavior of self-compacting concrete (SCC) and conventional concrete (CC) slender beams having the same compressive strength and make a comparison between the shear behavior of concrete beams. The experimental program included casting and testing eight beams with a constant size of 150mm height ×125mm width×1000mm length. Two coarse aggregate maximum sizes were used (10mm and 20mm) with SCC and CC in normal and high strength concrete. The results showed that increasing the coarse aggregate maximum size from 10mm to 20mm results in a slight increase in the diagonal cracking load and ultimate shear strength of SCC beams, while for CC beams the result was more significant. Also, it was found that the effect of increasing the coarse aggregate maximum size was more significant for normal strength as compared with high strength beams for both concrete types. Furthermore, the comparison between the shear behavior of SCC and CC beams having the same compressive strength and a concrete with the same coarse aggregate maximum size revealed that the SCC exhibited less diagonal cracking load and less ultimate strength compared with CC.